Bahan Bakar Padat Dari Tandan Kosong Sawit Menggunakan Proses Torefaksi; Variasi Suhu Dan Ukuran Bahan Baku - Eferius Mendrofa; Komalasari Komalasari; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm Empty Fruit Bunches (EFB) can be used as alternative energy source by using torrefaction process. Torrefaction is a pre-treatment process of biomass into solid fuel within temperature range of 200-300 oC in an inert condition. The aim of this research was producing solid fuel from oil palm EFB and studyng the effect of process variabel towards characteristic of solid fuel that was resulted. Torrefaction of EFB was using fixed bed horizontal reactor with temperature (225-275 oC) and particle size (5-15 mm). The quality of product that analyzed was calorific value, mass yield, energy yield and proximate (moisture content, ash content, volatile content and fixed carbon). The result of research was obtained for calorific value was 18362.17-20113.19 kJ/kg, mass yield was 52.15-77.85% and energy yield was 65.82-90.00%. The result proximate analysis such as moisture content was 1.22-1.35%, ash content was 6.97-13.59%, volatile content was 35.71-56.64%, and fixed carbon was 33.45-52.13%. From the result that was obtained, the effect of rising temperature given increasing to the calorific value, energy yield, ash content, and fixed carbon.Keywords: palm empty fruit bunches, biomassa, solid fuel, torrefaction.